MOBILE WEB-BASED INFORMATION SYSTEM MTs MA'ARIF KEPUTRAN - Primayoga, Bagus; Muslihudin, Muhamad (JECE (Journal of Ethics and Character Education), 2024)
Information System is an information facility to provide or convey information that will provide news or activities in the form of information of course it is not an easy thing for an institution or organization if it does not have an information system, it cannot be said that it is advanced with the information systems that exist today. At Madrasah Tsanawiyah Ma'arif Keputran there are a number of problems in the form of an information system that still uses bulletin boards and needs to be updated. With the development of the era, website-based information systems will later be designed and developed to provide information related to activities in madrasas. As well as making it easier for the teacher council or interested people in this madrasa to search for or to collect student data online. As well as being able to store a file or document so that it becomes more secure and practical. The data collection method used by the author is the method of observation, interviews and literature review. The developer method used is the waterfall method. In the information system built by researchers using editor software in the form of Visual Studio Code, Appserv, and MySQL. The results of this study will be in the form of an information system that will make it easier for users to find a madrasah. Besides that, it also makes it easier for an operator to store information data.